2022
DOI: 10.1063/5.0069432
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the homogeneity of energy conversion processes at dipolarization fronts from MMS measurements

Abstract: Please check and confirm the Funder(s) and Grant Reference Number(s) provided with your submission: Centre National d'Etudes Spatiales, Award/Contract Number Institut des sciences de l'ing enierie et des syste `mes, Award/Contract Number Please add any additional funding sources not stated above: Thank you for your assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…More importantly, the systematic and significant reversal in the current density pointed out in Alqeeq et al. (2022) as the cause of the reversal of the energy conversion process for the six analyzed DF events is confirmed by this statistical study as being a common signature of class II events. Although being small, we point out that the positive peak of the reversal of the current density after the DF crossing is obtained by three independent measurements (i.e., from pressure measurements ( J dia , Figure 7c), magnetic field measurements ( J curl , Figure 7d) and density and velocity measurements ( J part , Figure 7e)).…”
Section: Currents Density Structure Associated With Dfsupporting
confidence: 81%
See 3 more Smart Citations
“…More importantly, the systematic and significant reversal in the current density pointed out in Alqeeq et al. (2022) as the cause of the reversal of the energy conversion process for the six analyzed DF events is confirmed by this statistical study as being a common signature of class II events. Although being small, we point out that the positive peak of the reversal of the current density after the DF crossing is obtained by three independent measurements (i.e., from pressure measurements ( J dia , Figure 7c), magnetic field measurements ( J curl , Figure 7d) and density and velocity measurements ( J part , Figure 7e)).…”
Section: Currents Density Structure Associated With Dfsupporting
confidence: 81%
“…We have reported on a statistical study based on 132 DFs detected by the MMS mission during the full magnetotail season of 2017 (end of April to end of August). We found that the 132 events can be subdivided into two categories mostly according to their DF-shape (magnetic field profile): class I with 98 events (74.4%) for which the DF-shape shows a slow decrease of the magnetic field after the DF and is associated with smaller ion velocity, class II with 34 events (25.6%) for which the DF-shape shows the same time scale for the rising and the falling of the magnetic field (a bump) associated with minimums of ion and electron pressures and faster velocity as shown in Alqeeq et al (2022) for six DF events. These two classes can be considered as subcategories of the Schmid's DF category A (Schmid et al, 2015) as they both correspond to a decrease of the density and an increase of the temperature.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The right column of Figure 3 presents an example of a BBF front which satisfies the S11 criteria but not the F12-based criteria. This event was first reported by Alqeeq et al (2022) to show the non-homogeneity of the energy conversion due to electron-scale substructures attributed to lower-hybrid drift waves. Similar to the other example, t DF is accurately estimated as it corresponds to the ion energy enhancement (panel g), the ion density n i decrease (panel i) and the ion temperature T i increase (panel k).…”
Section: Resultsmentioning
confidence: 77%